CoFe2O4 nanoparticles decorated MoS2-reduced graphene oxide nanocomposite for improved microwave absorption and shielding performance. Issue 38 (15th July 2019) - Prasad, Jagdees; Singh, Ashwani Kumar; Haldar, Krishna Kamal; Tomar, Monika; Gupta, Vinay; Singh, Kedar
Abstract : Magnetic CoFe2 O4 nanoparticles decorated onto the surface of a MoS2 -reduced graphene oxide (MoS2 -rGO/CoFe2 O4 ) nanocomposite were synthesized by a simple two-step hydrothermal method. Abstract : Magnetic CoFe2 O4 nanoparticles decorated onto the surface of a MoS2 -reduced graphene oxide (MoS2 -rGO/CoFe2 O4 ) nanocomposite were synthesized by a simple two-step hydrothermal method. The electromagnetic (EM) wave absorption performance and electromagnetic interference (EMI) shielding effectiveness of the materials were examined in the frequency range of 8.0–12.0 GHz (X-band). The MoS2 -rGO/CoFe2 O4 nanocomposite was characterized by various tools such as X-ray diffraction, Raman spectroscopy, scanning electron microscopy, and transmission electron microscopy. High-resolution transmission electron microscopy results confirmed the decoration of magnetic nanoparticles onto the surface of the MoS2 -rGO nanocomposite with a diameter of 8–12 nm. The multiple interfacial polarization, moderate impedance matching, and defect dipole polarization improve the dielectric and magnetic loss of the materials, which leads to strong attenuation loss ability of incident EM energy within the shield. The pure MoS2 -rGO nanocomposite represents total shielding effectiveness (SET ∼16.52 dB), while the MoS2 -rGO/CoFe2 O4 nanocomposite exhibits total shielding effectiveness (SET ∼19.26 dB) over the entire frequency range. It may be explained that the magnetic nanoparticles (CoFe2 O4 ) serve as excellent conductive and magnetic fillers with a large surface area, leading to the migration of charge carriers at multi-interfaces.